1997
DOI: 10.1016/s0044-8486(97)00057-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of freeze-dried microalgal diets for the seed culture of Ruditapes decussatus using physiological and biochemical parameters

Abstract: This study evaluates the nutritional value of several species of freeze-dried microalgae used to feed the seed of Ruditapes decussatus. These microalgae were: Isochrysis galbana, clone T-ISO; Tetraselmis suecica; and Phaeodactylum tricornutum. The addition of antibiotics, kaolin and fresh microalgae to the freeze-dried diet was also evaluated, and a study was made of the nutritional value of one species of microalga in each of the four stages of preparation of the freeze-dried diet: culture; concentration; fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 29 publications
1
44
0
3
Order By: Relevance
“…The specific growth rate was calculated from the slope of the linear regression of log-transformed dry weight against age (Albentosa et al, 1997). The final biomass was calculated with the dry weight and the larval density was obtained at the end as described by (Cahu et al, 1998).…”
Section: Analysis Of Growth and Culture Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific growth rate was calculated from the slope of the linear regression of log-transformed dry weight against age (Albentosa et al, 1997). The final biomass was calculated with the dry weight and the larval density was obtained at the end as described by (Cahu et al, 1998).…”
Section: Analysis Of Growth and Culture Evaluationmentioning
confidence: 99%
“…The dissolved oxygen level (mg/l) and pH were measured daily. The ammonia and nitrite level at each tank were analyzed as described by Albentosa et al (1997).…”
Section: Analysis Of Growth and Culture Evaluationmentioning
confidence: 99%
“…Much research has been carried out also on broodstock conditioning (Ojea et al, 2008;Matias et al, 2009) and on diets for Venerupis decussata larvae Matias et al, 2011) and seed (Albentosa et al, 1996a(Albentosa et al, , 1996b(Albentosa et al, , 1996c(Albentosa et al, , 1997Lamela et al, 1996;Jara-Jara et al, 1997;Fernández-Reiriz et al, 1998Pérez Camacho et al, 1998Enes and Borges, 2003) in controlled conditions. Furthermore, a number of successful trials have demonstrated the feasibility of rearing this bivalve in different European countries (Walne, 1976;Breber, 1985;Pastore et al, 1996) using different culture techniques in the sea as well as in coastal lagoons (Chessa et al, 1998(Chessa et al, , 2005Pais et al, 2006b;Serdar et al, 2007).…”
Section: Rearing In Europementioning
confidence: 99%
“…The reduction in the number of particles as a function of time is monitored by taking water samples at fixed time intervals and measuring the particle concentration (Coughlan, 1969). Filtration rate was calculated using the following equation (Albentosa et al, 1997;Lora-Vilchis, 2001):…”
Section: Effects Of Current Velocitymentioning
confidence: 99%
“…Ingestion rate was calculated using the following equation (Albentosa et al, 1997, LoraVilchis, 2001 …”
Section: Effects Of Current Velocitymentioning
confidence: 99%